Claiming expertise from betwixt and between: Digital humanities librarians, emotional labor, and genre theory. Issue 2 (2nd October 2017) - Logsdon, Alexis; Mars, Amy; Tompkins, Heather
ABSTRACT: Librarians' liminal (intermediate) position within academia situates us to make unique contributions to digital humanities (DH). In this article, we use genre theory, feminist theory, and theories of emotional labor to explore the importance of discourse mediation and affective labor to DH and the interplay between these areas and academic structural inequality. By claiming our expertise and making explicit work that is often not visible, we can advocate for new and varied roles for librarians in digital humanities. Our analysis is informed by both theory and practice, and it takes a dialogic approach that depends upon the interactions between the two.